2013
DOI: 10.1186/1745-6673-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Work-related leukemia: a systematic review

Abstract: Leukemia is a complex disease, which only became better understood during the last decades following the development of new laboratory techniques and diagnostic methods. Despite our improved understanding of the physiology of the disease, little is yet known about the causes of leukemia. A variety of potential risk factors have been suggested so far, including personal habits and lifestyle, and a wide range of occupational or environmental exposures. A causal association with leukemia has only been documented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 98 publications
0
22
0
Order By: Relevance
“…Benzene belongs to the group of polycyclic aromatic hydrocarbons and is a known carcinogenic. It is found in gasoline and automotive exhaust, among other uses, such as paint industry, lacquers, varnishes, adhesives, glue, degreasing agents, cleaning products and detergents and are used in the production of dyes, plastic, agricultural products, pharmaceutical products and fabric industries 12,[28][29][30] . According to Uzma et al 31 , humans absorb about 50% of inhaled benzene depending on their concentration in the atmosphere and the level of exposure.…”
Section: Ggmentioning
confidence: 99%
See 2 more Smart Citations
“…Benzene belongs to the group of polycyclic aromatic hydrocarbons and is a known carcinogenic. It is found in gasoline and automotive exhaust, among other uses, such as paint industry, lacquers, varnishes, adhesives, glue, degreasing agents, cleaning products and detergents and are used in the production of dyes, plastic, agricultural products, pharmaceutical products and fabric industries 12,[28][29][30] . According to Uzma et al 31 , humans absorb about 50% of inhaled benzene depending on their concentration in the atmosphere and the level of exposure.…”
Section: Ggmentioning
confidence: 99%
“…Nevertheless, in our study, it was possible to observe the higher prevalence of leukemia in groups exposed to substances known to be leukemogenic. Several authors have observed the occurrence of leukemia in specific professional categories, recognizing them as more exposed to carcinogenic agents such as solvents, household sanitizers, formaldehyde and pesticides 12,39 . According to Chagas et al 38 , the main occupational carcinogenic agents (ionizing radiation, benzene, ethylene oxide), work sectors and processes, such as rubber industry and the shoe manufacturing and repair are risk factors for the development of leukemia types.…”
Section: Ggmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies show an association between IR at low doses (1 to 5 mGy) and development of leukemia. Leukemia is a complex disease that may have etiologies related to the lifestyle and occupational and environmental exposure, but there are also associations between leukemia (Polychronakis et al, 2013) due to genetic instability related to increased single and double strand DNA breaks that can lead to the chromosomal alterations and formation of MN (Saha et al, 2014), as noted in mutagenicity analysis of professionals occupationally exposed to IR in this study. There are also reports that IR can lead to apoptosis, as observed in embryonic neuronscells (Leuraud et al, 2015).…”
Section: Nuclear Changes Induced By Occupational Exposure To Ir In Ormentioning
confidence: 67%
“…While occupational exposures to some chemical and physical agents are known to be risk factors for several cancer types [7][8][9][10][11], little is known regarding the role of occupational factors in the development of meningioma [3]. Some studies have shown associations between specific works (e.g.…”
Section: Introductionmentioning
confidence: 99%